Exploring patient safety culture assessment among healthcare professionals in hospitals of Riyadh, Saudi Arabia - Alharbi, Mohammed Fayez J (2021)
Patient safety is an essential and vital component of healthcare quality. Despite constant vigilance, healthcare providers face many challenges in today’s healthcare environment in trying to keep patients safe. More people have died from medical errors than from automobile accidents, breast cancer, or acquired immunodeficiency syndrome (AIDS). Therefore, patient safety problems have become a major concern for healthcare organizations around the world in both rich and poor countries. Medical errors are becoming one of the leading causes of death as a result of the lack of validated tools that are suitable for assessing patient safety culture in Saudi hospitals. This is an important issue to investigate because doctors and nurses have been shown to have discrepant safety attitudes. It is on the basis of these concerns that this study intends to explore the extent to which patient safety culture practices are followed in Saudi Arabia hospitals. The study also probes the possible causes of the medical errors. The study goes further to assess- based on the medical staff standpoint and the international healthcare standards if the current measures are valid and reliable for use with the workforce in Saudi Arabian hospitals. Methodologically, the study employed qualitative method based on case study approach. The participants of the study that consisted of eight doctors and eight nurses from emergency departments of four selected hospitals in Riyadh, Saudi Arabia were selected through purposive sampling. Data were collected from face-to-face interviews which lasted for 60 minutes at the respective hospitals in doctor’s rooms and staff lounges during break time of each participant. They were interviewed about their involvements in the patient safety culture by their respective hospitals. The interview was conducted using the interview guide set by the researcher. Secondary sources (document analysis) were also used as a data source. NVIVO version 12 was used to manage, shape, and analyze the interview data. The study reveals that the major issues regarding patient safety are compliance based on awareness among medical personnel and work culture in the hospital. The issues also include validity and reliability of tool documentation and traceability, adequacy of patient safety measures, number of patients’ complaints, and the adaptation of safety measure by medical personnel. The study further reveals that the causes of medical errors are negligence and lack of discipline by medical staff, and lack of communication/ miscommunication between medical staff and patient. The study further elucidates that element that can help eliminate and mitigate errors are clear hospital policy and awareness training to medical staff. Based on the results, it is recommended that skilled health personnel should be given priority in being taken in as part of the medical staff. Furthermore, communication between the patients and medical staff should be enhanced. Finally, awareness among the medical staff should be enhanced to improve patient safety.